Eficiência dinâmica intertemporal dos gastos com serviços de abastecimento de água e esgotamento sanitário prestados por concessionárias regionais e microrregionais brasileiras - Cruz, Gilka Alice Alves da (2022)
Basic sanitation is defined as a grouping of measures whose objective is to preserve the environment, in order to prevent diseases and offer better health conditions to the population. In this sense, evaluating the economic-financial efficiency of these services is essential to understand the quality of the service in the country. Thus, the present study aims to measure the intertemporal dynamic efficiency of spending on public and private water supply and sewage services provided by Brazilian regional and micro-regional concessionaires from 2016 to 2020. This is a documentary study, of the descriptive type, with a quantitative approach. For the analysis of efficiency, the technique of intertemporal analysis dynamic DEA - DSBM was used with the basic sanitation service providers, in order to find the efficiency of the operators. The study sample is composed of 25 companies that provide water and sewage services in Brazil. The results show that the average efficiency of the sector was about 57.27% and that the concessionaires need to increase the investments made in order to universalize the provision of services. Most companies are public and regional and the level of efficiency is concentrated between poor and good. Thus, it is concluded that operators in the basic sanitation sector need to increase their level of efficiency to meet the goal of universalization of the sector for the year 2033.